Pengaruh Tingkat Pengangguran Pada Perekonomian Indonesia - Nafisah Lubis; Elvita Azzahra Lubis (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
As a participant in the G20 Group and the Association of Southeast Asian Nations (ASEAN), Indonesia actively supports sustainable economic growth. However, this nation has problems in absorbing labor, giving rise to concerns about poverty which can endanger social and political stability and impact the welfare of its population. Therefore, a study of the problem of poverty is needed. The aim of this research is to determine the effect of inflation, minimum wages in each province, and HDI (Human Development Index) on poverty levels in Indonesia. Using data collected from thirty-three provinces in 2015 and 2018, this research uses a panel-based regression technique with inflation, HDI, and provincial minimum salary as independent variables. Poverty is identified as the dependent variable. The findings of this study validate the effects of the fixed equality approach and demonstrate the large and detrimental impact of HDI and inflation on poverty in Indonesia. On the other hand, there is no real impact of the provincial minimum wage on poverty levels in this country. Governments can invest in developing people's skills and education, optimizing regional possibilities, and implementing efficient regulations to fight poverty. This research aims to determine the impact of inflation, minimum wages in each province, and the HDI, or Human Development Index, on poverty levels in Indonesia. Using data collected from 33 provinces between 2015 and 2018, this research uses panel data regression techniques with inflation, HDI and provincial minimum wages as independent variables. The dependency factor found was poverty. The conclusions of this research support the application of the fixed impact method and show how inflation and HDI have a significant negative influence on the number of poor people in Indonesia. In contrast, the provincial minimum salary does not have a significant effect on the national poverty level. To combat impoverishment, government agencies can invest in individual education and skills development, maximize local opportunities, and implement effective laws.